The Antiangiogenic Effect of Sanguinarine Chloride on Experimental Choroidal Neovacularization in Mice via Inhibiting Vascular Endothelial Growth Factor - Zhang, Junxiu; Mao, Ke; Gu, Qing; Wu, Xingwei (Frontiers in Pharmacology, 2021)
Background: The purpose of this study is to investigate the antiangiogenic effect of Sanguinarine chloride (SC) on models of age-related macular degeneration (AMD) both in vivo and in vitro. Methods: Choroidal neovascularization (CNV) was conducted by laser photocoagulation in C57BL6/J mice. SC (2.5 μM, 2 μL/eye) was intravitreally injected immediately after laser injury. The control group received an equal amount of PBS. 7 days after laser injury, CNV severity was evaluated using fundus fluorescein angiography, hematoxylin, and eosin (H&E) staining, and choroid flat-mount staining. Vascular endothelial growth factor (VEGF) expression in the retina/choroid complex was measured by western blot analysis and ELISA kit. In vitro, human retinal microvascular endothelial cells (HRMECs) were used to investigate the effects of SC on cell tube formation, migration, and cytotoxicity. The expression of the extracellular signal-regulated kinase (ERK)1/2, protein kinase B (AKT), mitogen-activated protein kinases (p38-MAPK) in vitro, and VEGF expression in vivo was also analyzed. Results: SC (≤2.5 μM) was safe both in vitro and in vivo. Intravitreal injection of SC restrained the formation of laser-induced CNV in mice and decreased VEGF expression in the laser site of the retina/choroid complex. In vitro, SC inhibited VEGF-induced tube formation and endothelial cell migration by decreasing the phosphorylation of AKT, ERK1/2, and p38-MAPK in HRMECs. Conclusions: SC could inhibit laser-induced CNV via down-regulating VEGF expression and restrain the VEGF-induced tube formation and endothelial migration. Therefore SC could be a potential candidate for the treatment of wet AMD.